Donald Trump’s Spheres of Influence Strategic Doctrine - Bradley Nelson (Journal Of Global Strategic Studies, 2025)
The second Trump administration is disrupting both longstanding U.S. foreign policy and the foundations of the liberal world order. Under Trump 2.0, America has junked its strategic policy of global liberal hegemony in favor of a doctrine of spheres of influence. At bottom, Washington now pursues a coercive, rapacious, power-driven approach to the broader Western hemisphere, threatening and bullying neighbors and allies, while at the same time leaving Russia and China with the requisite space and freedom to do as they wish in their own geopolitical backyards. The dramatic transformation in U.S. foreign policy is rapidly ushering in a new global order that is grounded in a tripolar structure (U.S., Russia, and China) that privileges great power interests and aggression at the expense of the old rules, norms, and institutions of the post-WWII era. As the old order is weakened if not wiped clean away, the international system today lacks firm guardrails, and the security of the global weak is especially at risk. What can somewhat ameliorate this emerging problem is a non-aggression compact, or even a concert, among the three superpowers, as this could dampen the prospect of a hegemonic war and keep each out of the others’ sphere of influence.